Cover Image. (26th July 2019) - Corliss, Bruce A.; Mathews, Corbin; Doty, Richard; Rohde, Gustavo; Peirce, Shayn M.
Abstract : Cover Artwork: The cover image is based on the Invited Review Methods to Label, Image, and Analyze the Complex Structural Architectures of Microvascular Networks by Bruce Corliss et al., https://doi.org/10.1111/micc.12520 .